Insertases scramble lipids: Molecular simulations of MTCH2 - Bartoš, Ladislav; Menon, Anant K; Vácha, Robert (Structure (London, England, 2024)
Scramblases play a pivotal role in facilitating bidirectional lipid transport across cell membranes, thereby influencing lipid metabolism, membrane homeostasis, and cellular signaling. MTCH2, a mitochondrial outer membrane protein insertase, has a membrane-spanning hydrophilic groove resembling those that form the lipid transit pathway in known scramblases. Employing both coarse-grained and atomistic molecular dynamics simulations, we show that MTCH2 significantly reduces the free energy barrier for lipid movement along the groove and therefore can indeed function as a scramblase. Notably, the scrambling rate of MTCH2 in silico is similar to that of voltage-dependent anion channel (VDAC), a recently discovered scramblase of the outer mitochondrial membrane, suggesting a potential complementary physiological role for these mitochondrial proteins. Finally, our findings suggest that other insertases which possess a hydrophilic path across the membrane like MTCH2, can also function as scramblases.
Keywords: insertase; scramblase; Cell Membrane; Molecular Dynamics Simulation; Lipids; lipidy; simulace molekulární dynamiky; membrane defect; free energy barrier; flip-flop rate; hydrophilic groove; molecular dynamics; buněčná membrána